Characteristics and control mechanism of melting process under extra magnetic force fields. (25th February 2020) - Dai, Renkun; Wu, Yining; Mostaghimi, Javad; Tang, Linghong; Zeng, Min
Abstract: Melting is an essential process in various industrial applications. Effective control and optimization of the melting process are in desperate need. Despite the commonly used control of energy input, extra forces can also produce sophisticated effects on the melting process. This present study aims to investigate the fundamental mechanism of melting control through extra force fields. The extra magnetic force fields are generated by the electrical coils on four different sides of the cavity. The basic melting characteristics are obtained using the enthalpy based lattice Boltzmann method. Results indicate that, when coils are on the bottom or left side, the increase of magnetic force would result in enhancement of the melting process. And it would result in suppression when coils are on the right side. Besides, it would result in suppression first and then enhancement when coils are on the top side, due to the competition of gravity. The underlying reason is that when coils are set on different sides, the angle between the given temperature gradient and the extra magnetic force varies. Basically it would result in enhancement when the angle increases. Otherwise it would result in suppression. This is the key to achieve different control effects.